A rare case of Gastric Diverticulum in a young patient - Soccol Fassina, Gabriel; Benincá Albuquerque, Antônio; Boeira Rovani, André Luca; Campos Horbach, Vitor; Giovelli, Mateus; Reffati, Diego; Navarini, Daniel (Clinical and Biomedical Research, 2024)
Gastric diverticulum represents a rare disorder of the gastrointestinal system. Although most patients are asymptomatic and the finding of this condition is often incidental, a large diverticulum may be related to upper abdominal pain, dyspepsia, nausea and emesis. In more severe cases, diverticula may cause ulcerations, perforation or even hemorrhage. The diagnosis is usually difficult, the symptoms can be common to a series of other gastrointestinal disorders, turning the anamnesis and physical examination not very specific. Esophagogastroduodenoscopy is recommended for correct visualization of the location and size of the lesion. Surgical resection is considered the main treatment of this condition in symptomatic patients or patients with complications. We describe the case of a young patient with diverticulum in the gastric fundus, and a brief review of the literature.